"Spinning" or rotational discus throwing
Some fotos and words about the "spinning" or rotational technique in discus throwing: Practice the spin first without the discus! Begin by stepping in from the back of the ring, landing near the center in the ball of the foot. Once the foot lands, push off with the other foot to start the spin. Continue the spin and land with the feet in the proper heel-toe alignment. The full spin: Note that when starting the back motion to begin the rotation, the shoulders are kept parallel to the ring surface. As the body starts to rotate, the weight is shifted from the right to the left foot. As the right foot comes around, it is kept relatively low with the shoulders remaining parallel to the ground. As the body continues to turn, balance must be maintained with the head remaining up. Don't look down during the spin. The final throwing motion starts from the feet, progressing up through the hips. As the discus starts to be brought forward, the other arm is collapsed toward the chest. The throwing arm should be moving upward as well as forward. As the discus is released, continue the spin until the front leg is over the center of the ring, them bring the foot quickly down to the ring surface. Spinning should be practiced on a daily basis. You don't have to throw a discus to practice. Draw a circle on the driveway or in the garage for practice. Tie a knot in a large hand towel and throw that in your practice spins. Perfect practice makes perfect!